2012
DOI: 10.1590/s0100-204x2012001000012
|View full text |Cite
|
Sign up to set email alerts
|

Produção de cachos e parâmetros genéticos de híbridos de caiaué com dendezeiro

Abstract: Resumo -O objetivo deste trabalho foi avaliar a produção de cachos e estimar os parâmetros genéticos de progênies F1 de caiaué (Elaeis oleifera) com dendezeiro (E. guineenses). As progênies foram plantadas em parcelas com número variável de plantas. Avaliaram-se número (NC), peso médio (PMC) e peso total de cachos (PTC) por planta, do sétimo ao décimo-terceiro ano após o plantio. Estes dados foram analisados por REML/BLUP em 59 progênies, com delineamento desbalanceado em linha e coluna. Todos os caracteres ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
14
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 9 publications
4
14
1
2
Order By: Relevance
“…Heritability values of 38, 36, and 45% were found in previous studies for the trait number of bunches in oil palm, açaí palm, and peach palm, respectively (Lopes et al, 2012;Farias Neto et al, 2008, 2013, consistent with the heritability value for TS found in the present study. In addition, Lopes et al (2012) reported a heritability value of 75% for the trait height of the first bunch, which is classified as high, as the value found for HFS.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Heritability values of 38, 36, and 45% were found in previous studies for the trait number of bunches in oil palm, açaí palm, and peach palm, respectively (Lopes et al, 2012;Farias Neto et al, 2008, 2013, consistent with the heritability value for TS found in the present study. In addition, Lopes et al (2012) reported a heritability value of 75% for the trait height of the first bunch, which is classified as high, as the value found for HFS.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, Lopes et al (2012) reported a heritability value of 75% for the trait height of the first bunch, which is classified as high, as the value found for HFS.…”
Section: Discussionmentioning
confidence: 93%
“…Similar results with high heritability in HIE OxG were presented by Gomes Junior et al (2014) and Lopes et al (2012), with higher heritability values among families than within families and with higher or equal heritability of MBW as the NB. High heritability estimates for NB (0.78), MBW (0.88) and TBY (0.70) were also reported by Okwuagwu et al (2008) for an oil palm population with wide genetic variability.…”
Section: Ra Gomes Junior Et Alsupporting
confidence: 86%
“…In the development of cultivars, genotypes with a very high MBW should be avoided, which can cause operational problems because the harvesting and manual loading of bunches is hampered, and the greater difficulty of industrial processing. Comparatively, Lopes et al (2012) reported a high positive correlation (0.52) between TBY and MBW and between TBY and NB (0.84) in HIE OxG, and almost zero between NB and MBW (0.06). High and positive correlations between NB and TBY (0.68 to 0.86) were found in oil palm populations evaluated by Okwuagwu et al (2008) and of 0.65 in a study of Okoye et al (2009).…”
Section: Ra Gomes Junior Et Almentioning
confidence: 92%
See 1 more Smart Citation